IDENTIFIKASI HAMA PENGGEREK DAUN Liromiza spp. (Diptera: Agromyzidae) DAN PARASITOIDNYA YANG BERASOSIASI PADA BERBAGAI JENIS TANAMAN SAYURAN DI KECAMATAN DETUSOKO DAN KELIMUTU KABUPATEN ENDE - Sri Wahyuni; Yustina Maria Silvia Wonga Puu; Kristina Erniyani; Julianus Jeksen (Agriculture Faculty of Flores University, 2008)
The aim of this research is to identify Liromiza spp. And the parasitoid is associated with various types of vegetable plants in Detusoko and Kelimutu Districts in Ende Regency. Data were analyzed by matching morphology of existing specimens with insect morphology books written by Bhorror 1970 and matching with standard specimens originating from Bali and Bogor. The results obtained from two vegetable producing districts in Ende, namely Detusoko and Kelimutu, show the following: There are two types of Liriomyza spp associated with several types of host plants in Ende Regency. L. huidobrensis (Diptera: Agromyzydae) is located in Kelimutu District and L Sativae (Diptera: Agromyzydae) is in Detusoko District. The diversity of parasitoids found in Detusoko Subdistrict were as many as four species from the Eulopidae family while in Kelimutu District there were five types of parasitoids originating from two families namely Braconidae and Euiopidae. Neosacharis okazaki is the most dominant type of parasitoid in each plant in Detusoko District. Opiits sp dominant in Kelimutu Subdistrict on the long bean, green beans, mustard greens, chicory and cabbage. While H. varicornis is dominant in Kelimutu District in tomato plants.